Komunikasi Budaya Marsialapari Suku Mandailing di Rabi Jonggor, Kecamatan Gunung Tuleh, Kabupaten Pasaman Barat - Nasution, Efrizal; Aisyah, Siti (Journal of Management, Education and Communication, 2024)
This research examines the cultural communication of marsialapari tradition and values ​​within Mandailing tribe in Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency. This research uses a qualitative descriptive research method. The research results show 1) The cultural communication process of the Marsialapari tradition is a series of verbal and non-verbal interactions between individuals or groups involved in the cultural practices. 2) The changes regarding attitudes in the marsialapari tradition of the Mandailing tribe due to the intervention of developed technology in the agricultural sector as well as agricultural land continue to shrink. 3). There are social values ​​within marsialapari tradition of the Mandailing tribe called "menoto" which can foster harmonious social relations and a system of mutual cooperation.